Structure and morphology of atomic layer deposition grown ZnO thin film/nanostructure on polymeric template. (2019) - Singh, Ajaib; Mathur, Aakash; Pal, Dipayan; Sengupta, Amartya; Singh, Rinki; Chattopadhyay, Sudeshna
Abstract: Zinc oxide (ZnO) was grown on polymer template, namely Poly (methyl methacrylate) (PMMA), by atomic layer deposition (ALD) technique. The detailed structural characterizations of the composite ZnO/PMMA film, through X-ray scattering techniques, indicate that on the PMMA template crystalline ZnO thin film was formed with its c-axis oriented along the surface normal. Combination of X-ray reflectivity (XRR) and atomic force microscopy (AFM) studies demonstrate the formation of high quality ZnO thin film (about 25 nm thick) on PMMA template, with more than 92% coverage and low surface/interface roughness. AFM results clearly show that the ZnO film consists of almost uniform nanoparticles with ∼24-30 nm in-plane size distribution, which is very much consistent with the observed size of the ZnO crystallites obtained from X-ray diffraction (XRD) study.